Evaluation of jennies' colostrum: IgG concentrations and absorption in the donkey foals. A preliminary study. Issue 8 (August 2020) - Turini, Luca; Bonelli, Francesca; Nocera, Irene; Battaglia, Federica; Meucci, Valentina; Panzani, Duccio; Mele, Marcello; Sgorbini, Micaela
Abstract: Immunoglobulin type G (IgG) concentration both in jennies' colostrum and in serum of donkey foals are mostly unknown in the first 24 h after delivery. The aims of the present study were to evaluate the IgG concentrations of colostrum during the first 24 h of lactation of Amiata jennies, the absorption of colostrum and the weekly body weight gain of the donkey foals. IgG concentrations were assessed in the jennies' colostrum and in the serum of donkey foals. Colostrum was collected in 9 jennies ready after delivery, and at 6, 12, 24 h after foaling from both halves. Serum was collected at the same sampling times from 9 donkey foals. Donkey foals were weighted at birth and then weekly until the 28 th days of life. Temporal changes of IgG concentrations in dam's colostrum and in donkey foal serum were analyzed by a linear regression model and a general linear model, respectively. Results showed that colostrum IgG concentration were similar between the left and the right half. Colostrum IgG concentrations decreased continuously throughout the time in all jennies by 0.0244 Log10 mg/mL per hour. Serum IgG concentrations in donkey foals at birth was significantly lower compared to other times. No correlation was found between the colostrum IgG concentrations and the average weekly body weight gain of the donkey foal. The pattern of colostrum IgG levels in jennies and serum IgG concentration in donkey foals seem to be similar to what reported for equine. However, the donkey foals seem to be less agammaglobulinemic at birth compared to the horse foal. The pattern and both serum and colostrum concentrations evaluated in the Amiata donkeys were slightly different from results reported in other donkey breeds, underlying the importance of setting references specific to breed. Abstract : Biology; Zoology; Veterinary medicine; Jenny; Donkey foal; Colostrum IgG; Serum IgG; Donkey foal weight